Community contextual effects on at‐risk mothers' engagement in Georgia's Maternal, Infant, and Early Childhood Home Visiting programme. Issue 4 (25th March 2018) - Cho, Junhan; Bae, Dayoung; Terris, Darcey D.; Glisson, Rachael E.; Brown, Anita
Abstract: The current study examined family and community factors related to home visiting programme engagement in a sample of 1, 024 mothers (primary caregivers, mean age 22.89 years) who participated in family support programmes funded through Georgia's Maternal, Infant, and Early Childhood Home Visiting programme. Using 2‐level hierarchical linear modelling, we examined the relationships between mothers' home visiting programme engagement and mothers' sociodemographic and community‐level risk factors. Higher sociodemographic risks, characterized by unstable romantic relationships, employment, low educational, and economic resources, were associated with less active home visiting engagement. Mothers who lived in communities with more challenging socio‐economic contexts, such as communities that had a higher proportion of divorced/separated households, poor quality housing conditions, and residential mobility, demonstrated lower programme engagement. Meanwhile, mothers who lived in communities that had a higher proportion of residents that did not finish high school demonstrated relatively higher programme engagement. The observed influence of community‐level factors remained significant after we controlled for mothers' sociodemographic characteristics. Although community‐level risks may appear outside the locus of control of home visiting, flexible programming and strategic partnerships with other community‐based resources, ones that explicitly take into account community‐level risks, may support improved home visiting engagement outcomes.